Pemberdayaan UMKM Tempe melalui Inovasi Produk dan Strategi Pemasaran Digital di Desa Joho Kabupaten Wonogiri - Yulinda Darwiyanti; Chindi Nur Laili; Rony Nursanto (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in boosting the local economy, particularly in rural areas. One emerging business opportunity in Joho Village, Purwantoro Subdistrict, Wonogiri Regency, is tempeh production, which is managed by local residents on a household scale. However, tempe MSME operators still face various challenges, such as limited product innovation, unattractive packaging, and marketing that remains conventional, resulting in relatively low product competitiveness. This study aims to analyze efforts to empower tempe MSMEs through product innovation and the implementation of digital marketing strategies to enhance business competitiveness and the village economy. The method used is a qualitative descriptive approach with data collection techniques through observation, interviews, documentation, as well as the implementation of training and mentoring for SME operators. The results of the study indicate that empowerment activities conducted through product innovation training, improved packaging quality, and the utilization of social media as a digital marketing tool are capable of enhancing the knowledge and skills of business operators in developing their businesses. Product innovations such as tempe chips, frozen tempe, and other tempe-based products add value to the goods produced. In addition, the implementation of digital marketing can expand market reach and increase consumer interest in tempe products from MSMEs. In conclusion, empowering MSMEs through product innovation and digital marketing strategies can be an effective step in enhancing business competitiveness and driving economic growth in the community of Joho Village, Wonogiri Regency. Keywords— SME Empowerment, Product Innovation, Digital Marketing, Rural Economy